(untitled) (Medico Legal Update, 2020)
Background/Objectives: In the dental environment, handpiece or ultrasonic scaler used in treatment causes aerosols and various pathogenic microorganisms. Many types of pathogens cause infectious diseases. This study is to identify surface disinfectants suitable for the management of Staphylococcus saprophyticus bacterial species, one of the causes of infection in medical institutions to use them as standardized surface management resources for infection control in dental clinic. Method/Statistical Analysis: Commonly used 7 types of disinfectants were classified to select commercialized disinfectants. Samples were taken by rubbing the surface of the unit chair with a sterile swab. In order to check the bacterial species cultured in the medium, a single colony was purely separated by streaking. To identify the bacterial species, DNA was extracted from the bacteria and PCR was performed. the mean and standard deviation of each group. One-way ANOVA and Scheffe’s post-test were carried out to identify the clear zone of paper discs and significant differences between groups. Findings: The test for bacterial identification was carried out for the surface flora of the unit chair. As a result, S. saprophyticus was identified on the surface. According to the result of comparative analysis of the clear zone size of each disinfectant, sodium hypochlorite (NaOCl), a chlorine disinfectant was found to have the highest disinfection effect (8.52mm), followed by Distell, an ammonium compound disinfectant (2.72). Improvements/Applications: The result of the analysis of the clear zone of the disinfectant showed excellent antibacterial activity in 0.3% NaOCl and 0.5% Distel, indicating that they are disinfectants suitable for S. saprophyticus used in the study.